1993
DOI: 10.1126/science.8105538
|View full text |Cite
|
Sign up to set email alerts
|

Transsynaptic Expression of a Presynaptic Glutamate Receptor During Hippocampal Long-Term Potentiation

Abstract: Repetitive activation of excitatory synapses in the hippocampus produces a persistent enhancement of synaptic efficiency known as long-term potentiation (LTP). In anesthetized and in freely moving rats, the induction of LTP in the perforant path led to a transient increase in the amount of messenger RNA (mRNA) coding for a presynaptic glutamate receptor (GR33) in dentate granule cells. The amount of GR33 mRNA was increased for at least 5 hours after the induction of LTP but was indistinguishable from control v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Thus, changes in the postsynaptic expression of proteins that are targeted to the presynaptic terminals during LTP could represent a good candidate mechanism underlying the propagation of long-lasting increases in synaptic strength within hippocampal circuits, a process that would have wide implications for a molecular mechanism involved in learning. Indeed, there is a precedent for both these ideas in previous studies investigating changes in the expression of the presynaptic protein, syntaxin 1B, which functions in the docking and priming of vesicles for calcium-dependent neurotransmitter release (Stidhof 1995) after induction of LTP (Smirnova et al 1993) and learning . Smirnova et al (1993) found a rapid and transient increase in the expression of syntaxin 1B in dentate granule cells after the induction of LTP at the perforant path-dentate gyrus synapses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, changes in the postsynaptic expression of proteins that are targeted to the presynaptic terminals during LTP could represent a good candidate mechanism underlying the propagation of long-lasting increases in synaptic strength within hippocampal circuits, a process that would have wide implications for a molecular mechanism involved in learning. Indeed, there is a precedent for both these ideas in previous studies investigating changes in the expression of the presynaptic protein, syntaxin 1B, which functions in the docking and priming of vesicles for calcium-dependent neurotransmitter release (Stidhof 1995) after induction of LTP (Smirnova et al 1993) and learning . Smirnova et al (1993) found a rapid and transient increase in the expression of syntaxin 1B in dentate granule cells after the induction of LTP at the perforant path-dentate gyrus synapses.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a precedent for both these ideas in previous studies investigating changes in the expression of the presynaptic protein, syntaxin 1B, which functions in the docking and priming of vesicles for calcium-dependent neurotransmitter release (Stidhof 1995) after induction of LTP (Smirnova et al 1993) and learning . Smirnova et al (1993) found a rapid and transient increase in the expression of syntaxin 1B in dentate granule cells after the induction of LTP at the perforant path-dentate gyrus synapses. Furthermore, an increase in the syntaxin 1B protein was observed in the terminal field of mossy fibers in CA3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3B). Whereas most studies on syntaxin 1A have focused on its intracellular functions, several reports suggested that it can adopt an extracellular localization as well (Brimhall et al, 1999;Smirnova et al, 1993a;Smirnova et al, 1993b).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence came from two main sources: the fact that inhibitors of either protein synthesis (Krug et al 1984;Otani & Abraham 1989;Frey & Morris 1997) or transcription (Nguyen et al 1994) affect the duration of LTP; and the finding that LTP itself induces transcriptional regulation of a variety of genes, including inducible transcription factors (Cole et al 1989;Wisden et al 1990;Abraham et al 1993;Worley et al 1993;French et al 2001) and genes encoding synaptic proteins (e.g. Smirnova et al 1993;Thomas et al 1994Thomas et al , 1996Link et al 1995;Lyford et al 1995;Bramham et al 1996;Hicks et al 1997;Génin et al 2001). Remarkably, experimental evidence also indicates that the expression of long-term memories shares many characteristics with LTP, including similar molecular mechanisms, a requirement for protein synthesis (Davis & Squire 1984;Meiri & Rosenblum 1998) and, in specific areas of the brain, the regulated transcription of a variety of genes (Nikolaev et al 1992;Davis et al 1996Davis et al , 1998Okuno & Miyashita 1996;Guzowski et al 1999Guzowski et al , 2001Tischmeyer & Grimm 1999;Hall et al 2000;Zhao et al 2000;Cavallaro et al 2001).…”
Section: Introductionmentioning
confidence: 99%